Biofilm formation on the surface of Ti–7.5Mo alloy after surface treatment - Pereira, Gilda [UNESP]; Souza, Marisa Aparecida [UNESP]; Escada, A. L. A. [UNESP]; Pereira, C. A.; Jorge, A. O. C. [UNESP]; Claro, Ana Paula Rosifini Alves [UNESP]; Rezende, Maria Cristina Rosifini Alves [UNESP] (Elsevier, 2013)
Purpose: In the present work, a susceptibility and efficacy of the Ti–7.5Mo alloy and Ti alloy to bacterial biofilm formation after surface treatment was evaluated. Methods and materials: The alloy Ti–7.5Mo was obtained in arc furnace under an argon atmosphere. Ingots were then homogenized under vacuum at 1100 °C for 86.4 ks to eliminate chemical segregation and after cold worked discs were cutting. Samples were immersed in NaOH aqueous solution (5 M) and treated at 450 °C. Biofilms were grown in Ti–7.5Mo discs immersed in sterile brain heart infusion broth (BHI)containing 5% sucrose, inoculated with microbial suspension (106 cells/ml) and incubated for 5 days. Next, the discs were placed in tubes with sterile physiological solution 0.9% sodium chloride (NaCl) and sonicated for to disperse the biofilms. Tenfold serial dilutions were carried and aliquots seeded in selective agar, which were then incubated for 48 h. Then, the numbers CFU/ml (log 10) were counted and analyzed statistically. Scanning electron microscopy (SEM) on discs with biofilms groups was performed, atomic force microscope (AFM) and contact angle. Results: The results show that there is a 5% difference in bacterial adhesion between pure titanium and Ti–7.5Mo alloy. Conclusion: It was concluded that the greater the roughness, the greater the hydrophilic effect.
Keywords: Biofilm; Titanium; Surface treatment